Integrated STEM PBL Model on Ecology and Biodiversity Topics to Equip Students with Problem-Solving Skills - Ermita Khoirumminsani Mita; Sudarmin; Risa Dwita Hardianti; Hendra Febriyanto; Siti Suhartini (Yayasan Darussalam Bengkulu, 2025)
Problem solving skills need to be developed so that students can compete with the rapid advances in technology and science.The purpose of this study was to find the improvement and response of students after the application of the STEM-based Problem Based Learning (PBL) model on Ecology and Biodiversity material on students' problem solving skills. The research method used is quantitative with quasi experiment. The research subjects were students of class VII G as the experimental class and class VII H as the control class. The results of the study were STEM-based Problem Based Learning (PBL) on ecology and biodiversity material proved effective in improving students' problem solving skills, based on the results of the Mann-Whitney test which showed a significant difference between the experimental and control classes. The conclusion in this study is that the STEM-based Problem Based Learning (PBL) model effectively improves problem solving skills in ecology and biodiversity materials. Problem solving skills need to be developed so that students can compete with the rapid advances in technology and science.